GDB pocket reference - Robbins, Arnold (O'Reilly, 2005)
"In the open source and free software worlds, GDB, or the GNU Debugger, is the standard debugger. It ships with all BSD and GNU/Linux systems, and compiles and works "out of the box" on just about every other kind of commercial Unix system. (It even works on Microsoft Windows systems!)" "Despite GDB's popularity, until now there hasn't been a brief guide or a quick reference to its many features. The GDB Pocket Reference fills this gap. It's designed so that you can look up features quickly and effectively. If you aren't a fluent user of GDB, the GDB Pocket Reference will show you what this debugger is capable of doing. If you are fluent, this book will keep the information you need right at your fingertips - without cluttering up either your physical or virtual desktop."--Jacket
Includes index. - Print version record
Keywords: Debugging in computer science -- Computer programs; Débogueurs; Debugging in computer science; Computer programs; Programming Languages; Operating Systems